A pious belligerence: dialogical warfare and the rhetoric of righteousness in the crusading Near East - Shachar, Uri Zvi (The Middle Ages series, 2021)
"This is a book about how Near Eastern communities clustered around pious warfare as a set of literary conventions and how these dialogical conventions infiltrated the semantics of contemporary authors"--